Bolts, double hexagon head, relieved shank, long thread, in heat resisting nickel base alloy NI-P100HT (Inconel 718), silver plated. Classification: 1275 MPa (at ambient temperature)/650°C. (15th June 1996) - British Standards Institution
No abstract available